ANALISIS KUALITASDESAIN KEGIATAN LABORATORIUM (DKL)MATERI PENCEMARAN LINGKUNGANJENJANG SMP DAN SMA - Sholeha, Shelly Dianita (2015)
PenelitianinibertujuanuntukmenganalisiskualitasDesainKegiatanLaboratorium (DKL)materipencemaranlingkunganjenjangSMPdanSMA.DesainKegiatanLaboratoriummerupakanpanduanpraktikumberupalembaraninstruksiyang terdiridarikomponen-komponenterstrukturuntukmengarahkanpembentukanpengetahuan.Kualitas DKL ditinjaudaristrukturdankemunculanranahkognitif.StrukturDKLdapatdianalisismenggunakankeberadaan diagram VeeuntukmenentukankelengkapanstrukturDKLdanskor diagram VeeuntukpenilaianstrukturDKL. Kemunculanranahkognitifdianalisisdengan menggunakantaksonomi Bloom revisi yang terdiridaridimensi proseskognitifdandimensipengetahuan. Sampel penelitiandiambildariperolehankeseluruhanDKLpencemaranlingkunganjenjangSMPdanSMA Negeri di kota Bandung.JumlahDKLyang dianalisisyaitu 5 DKLSMPdan 6 DKLSMA.DesainKegiatanLaboratoriumkemudian diujicoba, dianalisis, dandideskripsikan.HasildaripenelitianmengenaikelengkapanstrukturDKLberdasarkan diagram Vee, secaraumumDKLSMA memilikistrukturlebihlengkapdibandingkanjenjang SMP. Skoring diagram Veemenunjukannilai total rata-rata 8.8 padaDKLSMPdan 13.5 padaDKLSMA dari total skor 18. Hal inimenunjukanDKL jenjang SMP dan SMA memilikinilai yang tidaksempurnamenurut diagram Vee. HasilanalisisranahkognitifpadajenjangSMPdanSMAcenderungsamayaituterdapatpengetahuanfaktual, konseptualdanprosedural, namunkemunculandimensiproses kognitifberbeda, padajenjang SMPproseskognitifyang teridentifikasiC1 hingga C4, sedangkanpada SMA proses kognitif yang teridentifikasi C1 hingga C6 . Berdasarkantinjauankurikulum, keduajenjangtelahmencapairanahkognitif yangdiharapkanolehkompetensidasar. Kata kunci: Desain Kegiatan Laboratorium (DKL), Diagram Vee, Taksonomi The aim of this study is to analyze the quality of Design Laboratory Activity (DKL) in chapter environmental pollution for junior high school and senior high school level. Design Lab Activity is a practical guide formed as instruction sheet consists of components which structured to direct the formation of student's knowledge. The quality of DKL can be obtained from the structure and the emergence of cognitive domains. DKL structure can be analyzed by use the Vee diagram to determine the completeness of DKL's structure and Vee diagrams scores to assess DKL's structure. The emergence of cognitive domains is analyzed by using the revised Bloom's taxonomy consisting of dimensions of cognitive processes and dimensions of knowledge. Samples were taken from the overall acquisition DKL environmental pollution for junior high school and senior high school level in Bandung. The amount of DKL which analyzed; 5 for junior high school level and 6 5 for senior high school level. Design Laboratory Activity then tested, analyzed and described. Results of research on the completeness of structure DKL based Vee diagram, generally DKL for Senior High School level has a more complete structure than the Junior High School Level. The score from Vee diagram shows the average total value of 8.8 on DKL DKLfor junior high school level is 13.5 in the total score of 18. This indicate that both of DKL for junior high school and senior high school level have a value which are not perfect according to the Vee diagram. Results of analysis of cognitive domains on junior high school and senior high school level tend to be the same that there is a factual knowledge, conceptual and procedural, but the emergence of different dimensions of cognitive processes, the junior high school level cognitive processes are identified C1 through C4, while in senior high school cognitive processes were identified C1 to C6. Based on a review of curriculum, both levels have been reached cognitive expected by basic competence. Keywords: Design Activity Laboratory (DKL), Vee Diagram, Bloom's Taxonomy.